Peran Gender Pada Pengembangan Desa Wisata Lembah Asri Serang (D’LAS) Kecamatan Karangreja - Nofiyanti, Fifi; Nasution, Deivy Zulyanti; Pusparani, Pusparani (Jurnal Ilmiah Pariwisata, 2024)
This research aims to determine the role of gender in the development of the Asri Serang Valley (D'Las) tourist village, Karangreja District. Looking at the tourism aspect in Lembah Asri Serang Purbalingga can equalize gender roles, thereby reducing early marriages in the village. The research method used is a descriptive qualitative method. However, to complete the research data, respondent demographics are used. The research sample used incidental sampling. The results of the research showed that women were chosen to take care of work that was not too heavy and easy to do, and thought more about labor, namely finance, ticket keeper, homestay administrator. Mapping village potential, management, legality of village institutions, and village partnerships do not differentiate between women. There are equal gender roles in the development process of the Lembah Asri Serang (D'Las) tourist village. The role of gender in the element of marginalization of women does not occur in the development of this village, because women are given good positions, so that they can support work at tourist attractions better and more appropriately. It can be concluded that the role of gender in the development of the D'Las tourist village has a positive response to women to support and manage D'Las tourism, thereby making the Lembah Asri (D'Las) tourist village for the welfare of the community and reducing early marriage in Karangreja Village, Purbalingga. Keywords: gender roles, tourism village development, Asri D'Las Valley